2021
DOI: 10.1002/smll.202105303
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Interlayer Spacings of Hard Carbon Nanofibers Enables Enhanced Pore Filling Sodium Storage

Abstract: Hard carbon (HC) represents an attractive anode material for sodium‐ion batteries. However, most HC materials deliver limited capacity and the sodium storage mechanisms in the slope and plateau regions are controversial. Herein, a series of hard carbon nanofibers (HCNFs) with tunable interlayer spacings are designed to understand the sodium storage manners in HC. The optimized HCNFs featuring short‐range graphitic layers with sufficient interlayer spacings (0.37–0.40 nm) for Na+ intercalation deliver a high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 51 publications
2
66
0
Order By: Relevance
“…27−29 As the annealing temperature increases, the area ratio of the D 1 peak and G peak decreases gradually, indicating that the graphene carbon sheet structure becomes more orderly (the data in Table 2), which is consistent with the TEM results. 30 In addition, the ratio of I D3 / I G decreases from 1.90 to 0.29 with increasing annealing temperature, which means that the content of oxygen atoms and defects in HCs is reduced significantly, implying a more ordered carbon network. 31 N 2 adsorption/desorption measurements were performed to analyze the Brunauer−Emmett−Teller (BET) surface area and pore structure of HCs.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…27−29 As the annealing temperature increases, the area ratio of the D 1 peak and G peak decreases gradually, indicating that the graphene carbon sheet structure becomes more orderly (the data in Table 2), which is consistent with the TEM results. 30 In addition, the ratio of I D3 / I G decreases from 1.90 to 0.29 with increasing annealing temperature, which means that the content of oxygen atoms and defects in HCs is reduced significantly, implying a more ordered carbon network. 31 N 2 adsorption/desorption measurements were performed to analyze the Brunauer−Emmett−Teller (BET) surface area and pore structure of HCs.…”
Section: Resultsmentioning
confidence: 97%
“…The Raman spectra of HCs can be divided into four peaks at 1220, 1343, 1500, and 1595 cm –1 , which correspond to carbon atoms bonded by sp 2 –sp 3 bonds (D 4 ), carbon atoms at edges and defects of graphite sheets (D 1 ), the integrated heteroatoms (oxygen atoms) or five-numbered rings in carbon layers (D 3 ), and stretching vibrations of carbon atoms in sp 2 -hybridized graphite (G), respectively (Figure b). As the annealing temperature increases, the area ratio of the D 1 peak and G peak decreases gradually, indicating that the graphene carbon sheet structure becomes more orderly (the data in Table ), which is consistent with the TEM results . In addition, the ratio of I D3 / I G decreases from 1.90 to 0.29 with increasing annealing temperature, which means that the content of oxygen atoms and defects in HCs is reduced significantly, implying a more ordered carbon network …”
Section: Resultsmentioning
confidence: 99%
“…Since the sodium ions diffuse through the graphite layers to reach the closed pores, the structure order degree of the graphitic domains is decreased due to the interlayer expansion upon Na + intercalation. [ 31 ] Thus, it is concluded that the sodiation behavior of hard carbon below 0.07 V consists of Na + intercalation into the graphitic layers and Na deposition into the micropores.…”
Section: Resultsmentioning
confidence: 99%
“…An “ideal” carbon was thus supposed to combine large pores with an expanded interlayer distance of ≈3.65 Å, which could allow the diffusion of Na ions into the pores but not the electrolyte molecules. Similarly, Mai et al [ 134 ] investigated the Na‐storage property of hard carbon nanofibers (HCNFs) with tunable interlayer spacing, and reported that sufficient interlayer spacing (>0.37 nm) can provide diffusion channels for Na + to reach the enclosed pores for further filling.…”
Section: Na‐storage Models For Hard Carbonsmentioning
confidence: 99%